Facies Architecture and Diagenetic Features Development of Albian-Early Turonian Succession in Luhais Oil field, Southern Iraq - Jawad Abid, Noor; S. Al-Shaikhly, Saad; H. Al-Zaidy, Aiad Ali (Iraqi Journal of Science, 2023)
Clastic-carbonate succession which including the Nahr Umr and Mauddud Formations are represented a part of Albian-Early Turonian Sequence (Wasi`a Group). The present study includes Petrography, microfacies analysis, depositional environment, digenetic development, and reservoir characterization for seven boreholes (Lu-2, Lu-4, Lu-5, Lu-8, Lu-13, Lu-14 and Lu-39) within Luhais Oil field South Iraq.There are six type of carbonate microfacies were recognized in the Mauddud Formation:- Orbitolina - Milliolids wackestone to packstone Orbitolina wackestone to packstone, miliolids wackestone, Peloidal wackestone to packstone, Ooides to Peloids grainstone and bioclastic Wackestone - Packstone. These microfacies are represented three depositional environments: restricted shallow marine environment, semi-restricted shallow marine environment and Shoal environments. While the Nahr Umr Formation characterized by six lithofacies; Lithofacies I (Mudstone), Lithofacies II (Siltstone - Claystone), Lithofacies III (Lenticular Bedded Sandstone-Mudstone), Lithofacies IV (Falser Bedded Mudstone - Sandstone), Lithofacies V (Parallel Lamination Sandstone - Siltstone) and Lithofacies VI (Well sorted sandstone). These lithofacies are suggested four depositional environment of Nahr Umr Formation: Active channel environment, channel fill environment, delta plain environment and delta front and shore face environment.The most common diagenetic features observed and distribution in the studied sections includes Micritization, Cementation, Leaching (dissolution), dolomitization and Compaction fabrics. The most effective diagenetic processes were cementation, dissolution and dolomitization processes which have direct affect upon the study sections.The Nahr Umr and Mauddud sequence can be divided by the gamma ray and shale value into three zones (A, B and C); therefore we have interpretation of the logs porosity and porosity evaluation according to these divisions.